2013
DOI: 10.1111/jocd.12064
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in postmenopausal women: translation and validation of MSkinQOL questionnaire to measure the effect of a skincare product in USA

Abstract: This study shows that a careful translation and a rigorous process of validation lead to a reliable tool adapted to each country to explore and measure quality of life in healthy PM women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…compare the self-perceived effects of a facial anti-aging product to those automatically detected from selfie images of Chinese women of different ages and cities. 37 Although the use of an effective skin care regimen may not be expected to have an impact on the health status dimension, it has been reported that the use of an effective skin care regimen may have a positive effect on QoL 31 and we observed significant improvements for the vast majority of responses for the self-esteem and social effect dimensions. In previous publications on the role of estrogen HRT in skin aging, the visible signs of dryness, wrinkles, and sagging contributed to an increased perception of aging and decreased attractiveness 38 with a significant impact on QoL.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…compare the self-perceived effects of a facial anti-aging product to those automatically detected from selfie images of Chinese women of different ages and cities. 37 Although the use of an effective skin care regimen may not be expected to have an impact on the health status dimension, it has been reported that the use of an effective skin care regimen may have a positive effect on QoL 31 and we observed significant improvements for the vast majority of responses for the self-esteem and social effect dimensions. In previous publications on the role of estrogen HRT in skin aging, the visible signs of dryness, wrinkles, and sagging contributed to an increased perception of aging and decreased attractiveness 38 with a significant impact on QoL.…”
Section: Discussionmentioning
confidence: 48%
“…MSkinQoL was previously demonstrated to distinguish postmenopausal women from non‐menopausal women. After 4 weeks of treatment with a specially developed oil/water skincare product, the menopausal group showed improvements in their skin status as well as a concomitant but moderate improvement of the three MSkinQoL scores 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore and bearing in mind its possible contribution to psychological and emotional well‐being, it would seem important to investigate how much interest the general population give to esthetic dermatology. There have not been any findings related to this specific issue or any measurement (instruments) in this regard . Therefore, the main objective was to analyze the metric properties of a questionnaire which has been designed to show the perception of Spanish general emotional well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Many skin diseases are detrimental to social interactions, and thus it is important to evaluate their psychosocial effect as an aspect of the efficacy of treatment. Patients perceive a personal "disability" in different ways, which are not necessarily proportional to the clinical severity of disease [6][7][8]. Some reports claim that physical attractiveness influences an individual's QOL related to self-esteem and depression.…”
Section: Introductionmentioning
confidence: 99%